Inhibin B and anti-Müllerian hormone as markers of gonadal function after hematopoietic cell transplantation during childhood - Trivin Christine; Fischer Alain; Michon Jean; Baruchel André; Espérou Hélène; Brailly-Tabard Sylvie; Lemaire Pierre; Trabado Séverine; Couto-Sil; Laporte Sylvie; Brauner Raja (BMC, 2011)
Abstract Background It is difficult to predict the reproductive capacity of children given hematopoietic cell transplantation (HCT) before pubertal age because the plasma concentrations of follicle-stimulating hormone (FSH) and luteinizing hormone (LH) are not informative and no spermogram can be done. Methods We classified the gonadal function of 38 boys and 34 girls given HCT during childhood who had reached pubertal age according to their pubertal development and FSH and LH and compared this to their plasma inhibin B and anti-Müllerian hormone (AMH). Results Ten (26%) boys had normal testicular function, 16 (42%) had isolated tubular failure and 12 (32%) also had Leydig cell failure. All 16 boys given melphalan had tubular failure. AMH were normal in 25 patients and decreased in 6, all of whom had increased FSH and low inhibin B. Seven (21%) girls had normal ovarian function, 11 (32%) had partial and 16 (47%) complete ovarian failure. 7/8 girls given busulfan had increased FSH and LH and 7/8 had low inhibin B. AMH indicated that ovarian function was impaired in all girls. FSH and inhibin B were negatively correlated in boys (P < 0.0001) and girls (P = 0.0006). Neither the age at HCT nor the interval between HCT and evaluation influenced gonadal function. Conclusion The concordance between FSH and inhibin B suggests that inhibin B may help in counselling at pubertal age. In boys, AMH were difficult to use as they normally decrease when testosterone increases at puberty. In girls, low AMH suggest that there is major loss of primordial follicles.